2004
DOI: 10.1128/aac.48.6.2295-2297.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Cost of SCC mec and Methicillin Resistance Levels in Staphylococcus aureus

Abstract: Transformation of a type I SCCmec element into Staphylococcus aureus yielded highly oxacillin-resistant transformants with a reduced growth rate. Faster-growing variants could again be selected at the cost of reduced resistance levels, demonstrating an inverse correlation between oxacillin resistance levels and growth rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
123
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(128 citation statements)
references
References 13 publications
5
123
0
Order By: Relevance
“…MRSA strains that have been passaged to high-level vancomycin resistance and have retained methicillin resistance have converted to homotypic methicillin resistance (n ϭ 7; data not shown). Therefore, it may be that the mecA-associated fitness cost is a result of the conversion to the homotypic expression of methicillin resistance and not a direct consequence of increasing resistance to vancomycin, as previously shown by Ender et al (19). The conversion from heterotypic to homotypic methicillin resistance is not well understood.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…MRSA strains that have been passaged to high-level vancomycin resistance and have retained methicillin resistance have converted to homotypic methicillin resistance (n ϭ 7; data not shown). Therefore, it may be that the mecA-associated fitness cost is a result of the conversion to the homotypic expression of methicillin resistance and not a direct consequence of increasing resistance to vancomycin, as previously shown by Ender et al (19). The conversion from heterotypic to homotypic methicillin resistance is not well understood.…”
Section: Discussionmentioning
confidence: 92%
“…Ender et al found an inverse correlation between oxacillin resistance levels and growth rate by competing strains with heterotypic and homotypic expression of oxacillin resistance (19). Also, Katayama et al have shown that a naïve methicillinsensitive S. aureus strain did not tolerate the introduction of plasmid-borne, unregulated mecA, as mecA was often mutated or deleted to circumvent the expression of PBP 2a (28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the relative fitness of hospital-acquired MRSAs carrying the type I SCCmec element is reduced (Ender et al, 2004), whereas strains containing the smaller type IV element were not affected (Lee et al, 2007). It has also been shown in vancomycin-resistant MRSA strains containing the type II SCCmec element that deletion of mecA compensated for some of the fitness costs associated with becoming vancomycin resistant, suggesting that mecA is also costly (Noto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance-associated MGEs provide an advantage only in the presence of antibiotics. Otherwise, they can even be disadvantageous [17,18]. Thus, for such an element it is necessary to ensure its maintenance in the absence of selective pressure, e.g., if an antibiotic therapy was discontinued.…”
mentioning
confidence: 99%
“…Thus, for such an element it is necessary to ensure its maintenance in the absence of selective pressure, e.g., if an antibiotic therapy was discontinued. It can evolve to cause no or only minimal disadvantage in the absence of antibiotics, as it is the case for SCCmec type IV [17,18], to impose a selective pressure by itself [19] or, alternatively, to encode a factor conferring a selective advantage independently of the presence of antibiotics. Since experimental data show an influence of PSM-mec on virulence and/or biofilm formation [2,20], its presence might be a key factor for the evolutionary success (i.e., the pandemic spread and abundance) of SCCmec II and III elements and their host strains such as ST239-MRSA-III and ST5/ST225-MRSA-II.…”
mentioning
confidence: 99%